Nursing students' awareness on hand hygiene - Tulin Yildiz; Ebru Onler; Gönül Akcay (National Scientific Medical Center, 2020)
Objective: The study has been implemented to identify hand hygiene awareness of potential healthcare professionals who study at Nursing Department affiliated to two public universities. Material and methods: This was a descriptive research study, the research was in the nursing students (2, 3, 4 class) of two state universities between February and March 2017. Department of two selected public universities whereas the sampling covered 902 students, currently present at school, during the time of research as well as having approved to take part in the study. The data was analysed via computer-based methods including frequency (percentage) analysis, t test, Mann-Whitney U and Chi-Square tests. The scores were accepted significant within 95% reliability scale at p<0.05 significance level. Results: 775 students responded positively (85.9%) to the statement saying "healthcare professionals' hands become a risk factor for microorganism transfer to patients" compared to 127 participants who responded negatively (14.1%). The statement proposing "your insufficient hand hygiene practices become a reason for cross-contamination of hospital infections" was responded positively (87.3%) by 787 participants whereas negatively (12.7%) by 115 students. The presumption on microorganisms' transfer to patients usually done by healthcare professionals' hands was responded positively by sophomore students at 79.3% has been found  statistically and significantly lower than the juniors' positive  response rate (88.5%) and seniors' similar responses (89.7%) (X2=15.960; p=0.000). Conclusion:  The results display that awareness of nursing students on hand hygiene has gender-based and class-based variations. It is assumed that keeping up hand hygiene trainings at each year will possibly increase the awareness of nursing students.